Isolation and Characterization of Cultivable Microbes from the Gut of Zophobas atratus (Coleoptera: Tenebrionidae) Larvae Reared on Two Types of Artificial Diets - Vladislava Baklanova; Alexander Kuprin; Ivan Baklanov; Vadim Kumeiko (Biology)
Gut microbes are important for saproxylophagous insects, but little is known about the specific types of microbes that we can grow in the lab and how their diet affects them. We characterized aerobic culturable microbes from the superworm Zophobas atratus larvae reared on a standard diet (SD) and a fungal-based diet (FD) using the selective plating and 16S rRNA sequencing of isolates. Five functional groups were cultured: amino acid autotrophs, enterobacteria, yeasts, cellulolytic bacteria, and molds. A quantitative assessment revealed distinct diet-dependent patterns: SD-fed larvae showed the dominance of enterobacteria and amino acid autotrophs, while FD-fed larvae exhibited a higher abundance of enterobacteria and yeasts. Mold populations remained minimal under both diets. A phylogenetic analysis of bacterial isolates showed four core bacterial phyla (Pseudomonadota, Actinobacteria, Bacillota, and Bacteroidota) with diet-sensitive genus-level variations. Pseudomonadota dominated both diets, but certain genera were associated with different diets: Micrococcus and Brucella in the SD versus Citrobacter and Pseudomonas in the FD. Shared genera (Klebsiella, Enterobacter, and Bacillus) may represent a core culturable community. These findings demonstrate the influence of diet on culturable gut microbes while highlighting the need for complementary molecular approaches to study unculturable taxa. The isolated strains provide resources for investigating microbial functions in insect nutrition.